2018
DOI: 10.1111/tan.13447
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐A*02 repertoires in three defined population groups from North and Central India: Punjabi Khatries, Kashmiri Brahmins and Sahariya Tribe

Abstract: The allelic family of HLA‐A*02 with a repertoire of approximately 1022 alleles represents the predominant and most heterogeneous group at the HLA‐A locus. This remarkable diversity signifies its evolutionary relevance. Its population‐specific diversity is attributed to environmental factors and pathogen pressure and can be harnessed in biology and medicine, particularly in disease association and for HLA‐based vaccination approaches. We therefore investigated the HLA‐A*02 repertoire in two North Indian caste p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…This included A*02:01, *02:03, *02:05, *02:06, *02:07, and *02:11, of which A*02:11 exhibited highest occurrence at the repertoire level. 37 Notably, A*02:11 allele seems to be common in Indian populations, while it is completely absent in Caucasian and oriental populations. The frequency and diversity of certain alleles of HLA-A*02 were also reported to be high in African populations.…”
Section: Role Of Angiotensin-converting Enzyme 2 Gene In Entry Of Sars-cov-2: the First Genetic Gatewaymentioning
confidence: 99%
“…This included A*02:01, *02:03, *02:05, *02:06, *02:07, and *02:11, of which A*02:11 exhibited highest occurrence at the repertoire level. 37 Notably, A*02:11 allele seems to be common in Indian populations, while it is completely absent in Caucasian and oriental populations. The frequency and diversity of certain alleles of HLA-A*02 were also reported to be high in African populations.…”
Section: Role Of Angiotensin-converting Enzyme 2 Gene In Entry Of Sars-cov-2: the First Genetic Gatewaymentioning
confidence: 99%
“…Our study has been conducted on a more homogeneous group of patients representing predominantly the Hindu population from the four North Indian states of Punjab, Haryana, Uttar Pradesh and Delhi. It may be mentioned that the Indian subcontinent is characterized by high degree of genetic diversity of HLA and may be of other genes, for which high microbial pressure has been attributed as one of the responsible factors 30,31 …”
Section: Discussionmentioning
confidence: 99%
“…It may be mentioned that the Indian subcontinent is characterized by high degree of genetic diversity of HLA and may be of other genes, for which high microbial pressure has been attributed as one of the responsible factors. 30,31 Acute humoral rejection due to preformed MICA antibodies in the absence of HLA-DSA has earlier been demonstrated by Sumitran-Holgersson et al 17 as early as in 2002. Several studies subsequently also reported a significant correlation of both pre-and post-transplant MICA antibodies with adverse graft outcome.…”
Section: Patients Developing De Novo Dsamentioning
confidence: 92%
“…Analysis of SARS-CoV and SARS-CoV-2 proteomes for prediction of the MHC class I epitope revealed that HLA-A*02:03 and A*31:01 are as effective antigen presenters for COVID-19 indicating that these alleles might provide protection for their carrier individuals, whereas HLA-A*03:02 seems to be a risk factor [75] Population-specific HLA alleles is another concept for describing susceptibility of different populations to COVID-19. For instance, protective HLA-A*02 alleles were shown to have high frequencies among Indian African populations [78,79]. On the contrary, the susceptibility allele HLA-B*46:01 is highly distributed in South East Asia and rarely in Europe, while in Indian and African populations it is completely absent [80].…”
Section: Immunogenetics In Covid-19 231 Hlamentioning
confidence: 99%